Strategy, structure and culture: Cadbury, divisionalization and merger in the 1960s - Rowlinson, Michael (Journal of Management Studies, 2007)
This case study re-examines the history of Cadbury, the British-based chocolate confectionery manufacturer, to give an insight into the relationship between strategies of diversification, adoption of a multidivisional structure, and culture in relation to labour management. During the 1960s Cadbury undertook diversification, divisionalization and merger, all of which were affected by, and had an effect upon the Cadbury culture developed at the Bournville factory in Birmingham, England. Contemporaneous documentary evidence, especially the Cadbury board minutes, are used to question the prevalent view, mostly based on retrospective interviews with managers, that cultural change was the outcome of intended management strategies. Instead it is argued that the dilution of the Cadbury culture was the unintended consequence of diversification and divisionalization rather than a conscious abandonment on the part of a new generation of Cadbury directors or the influence of Schweppes after the merger with Cadbury.
Keywords: Teaching Business History